2012
DOI: 10.1007/s11033-012-1487-1
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 gene polymorphism and essential hypertension: an updated meta-analysis involving 11,051 subjects

Abstract: The polymorphisms of angiotensin-converting enzyme 2 (ACE2) gene have been suggested to be linked to increase risk of essential hypertension in multiple populations. However, the results are still debatable. To assess the association between ACE2 G8970A genetic polymorphism and essential hypertension, we conducted a meta-analysis of case-control studies across different ethnicity. PubMed, Embase, CBM, Wanfang and VIP databases were searched, and a total of 11 separate studies in females and nine separate studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 34 publications
4
63
0
3
Order By: Relevance
“…In accordance with the function of the renin-angiotensin system in regulating blood pressure and fluid balance, numerous studies have attributed genetic differences in risk of hypertension to variation in ACE2 , 44 although no studies have reported association with any pain or sensory symptoms. Angiotensin related peptides have been posited as neurotransmitters in the periaqueductal gray 55 and other pain relevant brain areas, where they modulate pro-and anti-nociceptive pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the function of the renin-angiotensin system in regulating blood pressure and fluid balance, numerous studies have attributed genetic differences in risk of hypertension to variation in ACE2 , 44 although no studies have reported association with any pain or sensory symptoms. Angiotensin related peptides have been posited as neurotransmitters in the periaqueductal gray 55 and other pain relevant brain areas, where they modulate pro-and anti-nociceptive pathways.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence suggests that ACE2 gene polymorphisms were associated with left ventricular hypertrophy (4144), coronary heart disease and myocardial infarction (45), cardiac remodeling and urinary protein level in men with type 2 diabetes and coronary heart disease (46) as well as with hypertension (42;47;48), hypertension in women (49) and antihypertensive response to ACE inhibitors in women (50). On the other hand, some reports found no association between ACE2 and hypertension (51;52) and ACE2 and a risk for sudden cardiac death in women or men (53) underlining the necessity for further evaluation of the impact of ACE2 gene variants on cardiovascular disease in human population.…”
Section: Ace2 and Cardiac Diseasementioning
confidence: 99%
“…A meta-analysis of caseecontrol studies across different ethnicities, including 7251 hypertensive patients and 3800 normotensive controls, suggests that ACE2 gene polymorphism G8790A is probably a genetic risk factor for essential hypertension across different ethnic populations in female subjects and in HanChinese male subjects [39]. Whether this polymorphism contributes to the risk of atherosclerosis development is yet to be investigated although it has not been highlighted in genome wide association studies which have been currently published.…”
Section: Ace2 In Human Atherosclerosismentioning
confidence: 99%